Pattern of adverse drug reactions into psychiatric patients - Barvaliya, Sandip; Panchal, Jigar R.; Desai, Mira K.; Parikh, Minakshi (International Journal of Basic & Clinical Pharmacology, 2019)
Background: To analyse adverse drug reactions (ADRs) reported in patients prescribed psychiatric medications at tertiary care hospital. Methods: ADRs reported in psychiatric patients between January 2011 to June 2017 were analyzed for demographic details, causal drugs, system organ classification, causality assessment (WHO-UMC criteria and Naranjo’s scale), preventability (Modified Schumock and Thorton’s criteria) and severity (Hartwing scale). Results: A total 4368 ADRs were reported during study period, out of which 658 (15.06%) were in psychiatric patients. The mean age of patients was 38±13.34 years and men (57.3%) were most commonly affected than women (42.7%). The most common causal drug groups were antidepressants (29.48%) followed by antipsychotics (23.12%) which include drug fluoxetine (33.9%) and olanzapine (34.3%) respectively. The most common system involved were central nervous system (32.8%) followed by gastrointestinal system (22.8%). Most of ADRs (42.7%) were observed after one month of therapy and showed possible (77%) causal relation with drug therapy. Majority of ADRs (77.4%) were not preventable and mild in nature (83.3%). Conclusions: ADRs are commonly seen in psychiatric patients. Hence, their monitoring and assessment in these patients who require multidrug and long-term therapy may help improve patient management.